Bridging Africa's income inequality gap: How relevant is China's outward FDI to Africa? - Isaac Kwesi Ofori; Toyo A. M. Dossou; Simplice Asongu; Mark Kojo Armah (African Governance and Development Institute (AGDI), 2021)
In line with the SDG 10 and Aspiration 1 of Africa's Agenda 2063, this study examines whether: (i) the remarkable inflow of Chinese FDI to Africa matters for bridging the continent's marked income inequality gap, (ii) Africa's institutional fabric is effective in propelling Chinese FDI towards the equalisation of incomes in Africa, and (iii) there exist relevant threshold levels required for the various governance dynamics to cause Chinese FDI to equalise incomes in Africa. Our results, which are based on the dynamic GMM estimator for the period 1996 - 2020, reveal that though: (1) Chinese FDI contributes to equitable income distribution in Africa, the effect is weak, and (2) Africa's institutional fabric matters for propelling Chinese FDI towards the equalisation of incomes across the continent, governance mechanisms for ensuring political stability, low corruption, and voice and accountability are keys. Finally, critical masses required for these three key governance dynamics to propel Chinese FDI to reduce income inequality are 0.8, 0.5 and 0.1, respectively. These critical masses are thresholds at which governance is a necessary but no longer a sufficient condition to complement Chinese FDI in order to mitigate income inequality. Hence, at the attendant thresholds, complementary policies are worthwhile. Policy recommendations are provided in the end.
Keywords: F6; F15; O43; O55; R58; 330; Africa; Agenda 2063; China; Corruption; Governance; FDI; Income Inequality